AN ANALYSIS OF BLENDED LEARNING IN ENGLISH EDUCATION DEPARTMENT OF UIN SULTHAN THAHA SAIFUDDIN JAMBI - Nurhasanah, Amalia; Mesalina, Juliana; Ulfahasanah, Yossi (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2020)
This research aims to discover third-semester students' perceptions of integrated learning in speaking skills implemented during the previous two semesters at the English Education Study Programme at the State Islamic University of Malaysia. The Sulthan Thaha Saifuddin Jambi University. The researcher carried out a qualitative investigation. Through interviews, information is collected. The researcher employed a technique of purposive sampling by selecting 10 students from each third-semester class based on information gleaned from their classmates and previous grades. This research included 30 participants. 15 open-ended questions were developed based on Schiffman and Kanuk's (2004) theory, the CAC model, which incorporates cognitive, affective, and conative components. Positive and negative perceptions of integrated learning in speaking classes over the past two semesters are revealed by the study's findings. Positive perceptions of the cognitive component include the ability to reduce the spread of Covid-19 at the time, the use of technology that is currently being developed in the education world, and the capacity to locate information from a variety of sources. Positive perceptions in the affective component, such as learning, can be achieved at any time and in any location. Nonetheless, there are negative perceptions, such as in the cognitive component, due to the lecturer's material being indistinct and the students' pronunciation being difficult to understand due to the poor internet connection. While the negative perception of the affective component is that students cannot manage their time between an online and offline discussion of the next topic, this is not the case. In contrast, the conative component focuses on the absence of interaction between new students and the content of online classes. In fact, some of the difficulties they encountered during the previous two semesters included a poor internet connection, the absence of an internet bundle on campus, and the separation of online and offline instruction.